2004
DOI: 10.1016/j.jpainsymman.2003.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Use of strong opioids in advanced cancer pain: a randomized trial

Abstract: The World Health Organization (WHO) guidelines for the treatment of cancer pain recommend nonopioid analgesics as first-line therapy, so-called "weak" analgesics combined with nonopioid analgesics as second-line therapy, and so-called "strong" opioids (with nonopioid analgesics) only as third-line therapy. However, these guidelines can be questioned with regard to the extent of efficacy as well as the rationale for not using strong opioids as first-line treatment, especially in terminal cancer patients. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 23 publications
2
106
1
6
Order By: Relevance
“…Therefore, a RCT is required to be conducted for the role of 2 nd step (Marinangeli et al, 2004;Maltoni et al, 2005;.…”
Section: Who Guideline For Steps and Pharmacological Treatmentmentioning
confidence: 99%
“…Therefore, a RCT is required to be conducted for the role of 2 nd step (Marinangeli et al, 2004;Maltoni et al, 2005;.…”
Section: Who Guideline For Steps and Pharmacological Treatmentmentioning
confidence: 99%
“…On the other hand, two randomized controlled trials demonstrated that using a Step 3 opioid first (two-step strategy) is significantly more effective than using the three-step strategy, in improving cancer pain (36,37). However, some adverse events such as nausea or constipation tended to be more frequent in the two-step strategy group in these studies.…”
Section: Patients With Moderate-to-severe Pain or Inadequately Contromentioning
confidence: 85%
“…Given the wide interindividual variability in the response to a specific opioid, it is important to know the pharmacological differences between them. There is no proven evidence that one opioid agonist is better than another as first-line therapy [12,37].…”
Section: Opioidsmentioning
confidence: 99%
“…Tramadol is well tolerated and has low addictive potential [38]. For several years now, it has been suggested in clinical trials that strong opioids can prove useful as first-line treatment, especially of terminal cancer pain [37]. Some organizations, such as the National Comprehensive Cancer Network (NCCN) currently recommend considering the option of low doses of strong opioids for this group of patients (Table 2) [36,39,40].…”
Section: • Tramadolmentioning
confidence: 99%